Pathologic studies of fatal cases in outbreak of hand, foot, and mouth disease, Taiwan. - Shieh, W J (Centers for Disease Control and Prevention, 2001)
In 1998, an outbreak of enterovirus 71-associated hand, foot, and mouth disease occurred in Taiwan. Pathologic studies of two fatal cases with similar clinical features revealed two different causative agents, emphasizing the need for postmortem examinations and modern pathologic techniques in an outbreak investigation.